ВОЛНОВЫЕ ПРОЦЕССЫ В ЭЛЕКТРОМЕХАНОГИДРАВЛИЧЕСКОЙ СИСТЕМЕ ПРИ ПУСКЕ ЭЛЕКТРОПРИВОДА НАСОСНОГО АГРЕГАТА - Клепиков, В.Б.; Коротаев, П.А. (Інститут електродинаміки НАН України, Київ, 2014)
Research of the pump unit start-up processes on the water supply system representing the line with distributed parameters is executed. The schedules displaying wave processes in a water supply system at pump units start-up are provided. It is shown that these processes lead to pressure increase in the highway and can be the main cause of water supply systems rushes. Possibility of pressure decrease is shown by means of the adjustable electric drive. References 3, figures 4.